PENGARUH KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUASAN KONSUMEN PADA PRODUK IPHONE DI KOTA BENGKULU - Selvi Desta Sari; Mardhiyah Dwi Ilhami (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2023)
This study aims to determine the effect of product quality and brand image on consumer satisfaction (a case study on students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu). This type of research is called quantitative descriptive research. The subject of this research is the students of the Faculty of Economics and Business, University of Muhammadiyah Bengkulu. The sampling method is accidental sampling. The number of respondents in this study was 150 respondents. The method of data collection is using a questionnaire spreader. The data analysis technique used multiple linear regression analysis and hypothesis testing, namely the t-test and f-test. The results showed that product quality had a positive and significant influence on consumer satisfaction with iPhone products in Bengkulu City. Brand image has a significant effect on consumer satisfaction with iPhone products in Bengkulu City. Partially, the two variables of product quality and brand image have a positive and significant influence on consumer satisfaction.